The 1st International Electronic Conference on Food Science and Functional Foods 2020
DOI: 10.3390/foods_2020-07747
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Nanomaterial Applications for Food Packaging and Preservation: Safety Issues and Risk Assessment

Abstract: The contribution of nanomaterials to the development of food packaging systems has been enormous in last years. Nanomaterial is defined as material having one or more dimensions in the range of 1–100 nm. Nano-sized materials change their optical, magnetic, electrical, and other properties, and for this reason are widely used in food packaging. Nanoparticles (NPs), nanocomposites (NCs), nanoclays (NCs), nanoemulsions (NEs), nanosensors (NSs), and nanostructures (NSTs) are some of the important nanomaterials tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(41 reference statements)
2
1
0
Order By: Relevance
“…From the data reported in Table 2, it was found that oleic acid was the highest (74.46%), while linolenic acid was the lowest (0.51%) in the KVOO. These results agreed with Agriopoulou et al [34], who found that the Koroneiki olive cultivar had a mean value of 76.70 % for C18:1 and 0.68 % for C18:3.…”
Section: Fatty Acids Compositionsupporting
confidence: 92%
See 2 more Smart Citations
“…From the data reported in Table 2, it was found that oleic acid was the highest (74.46%), while linolenic acid was the lowest (0.51%) in the KVOO. These results agreed with Agriopoulou et al [34], who found that the Koroneiki olive cultivar had a mean value of 76.70 % for C18:1 and 0.68 % for C18:3.…”
Section: Fatty Acids Compositionsupporting
confidence: 92%
“…The total amount of phytosterols found in KVOO was 1080.82 ppm. This finding was in line with that of Agriopoulou et al, [34], who said that the total amount of phytosterols in the Messinian region's cv Koroneiki was 1033.3 ppm. The purity of VOO can almost entirely be predicted by the phytosterol profile.…”
Section: Phytosterol Compositionsupporting
confidence: 91%
See 1 more Smart Citation